Effectivity of Opioid Rotation Compared to Opioid Combination for Cancer Pain: An Evidence Case Report - Faisal, Edward; Puspadina, Shafira; Puranto, Rudi; Shatri, Hamzah (Jurnal Penyakit Dalam Indonesia, 2022)
Pain is the main symptom in cancer patients that needs to be addressed immediately because it can reduce the quality of life. Concern or the ineffectiveness of using one type of opioid makes it necessary for clinicians to understand how to rotate opioids. Therefore, this evidence-based case report was conducted to identify the effectiveness of opioid rotation and combined opioids for the cancer pain management through a literature search on three databases. Literature searching was performed by using Pubmed, Cochrane library, and EBSCO according to clinical inquiries. Of the 24 studies obtained, only one study met the criteria and was then critically assessed. The study found that pain score in both opioid rotation group (fentanyl transdermal) and combined opioids group (oral oxycodone and fentanyl transdermal) was decreased from 2.9 to 2.0 (p=0.22) and 3.0 to 1.8 (p<0.06), respectively. In addition, therapeutic success was achieved in 11 patients in the opioid rotation group and 12 patients in the combined opioids group (p=0.98). Based on the study, it can be concluded that opioid rotation is as effective as combined opioids in managing pain in cancer patients.